You Cannot Go Home: Routine Concussion Evaluation is not Enough. Issue 4 (April 2015) - Hartwell, Jennifer L.; Spalding, M. Chance; Fletcher, Brian; O'Mara, M. Shay; Karas, Chris
Traditional care of mild traumatic brain injury (MTBI) is to discharge patients from the emergency department (ED) if they have a Glasgow Coma Score (GCS) of 15 and a normal head computed tomography (CT) scan. However, this does not address short-term neurocognitive deficits. Our hypothesis is that a notable percentage of patients will need outpatient neurocognitive therapy despite a reassuring initial presentation. This is a retrospective review of patients with MTBI at an urban Level I trauma center. Inclusion criteria were a diagnosis of MTBI in patients 14 years old or older, GCS 15, negative head CT scan, a completed neurocognitive evaluation, blunt mechanism, and no confounding psychiatric comorbidities. Six thousand thirty-two patients were admitted over 18 months. Three hundred ninety-five patients met inclusion criteria. Average age was 38 years (range, 14 to 93 years), 64 per cent were male, and mean Injury Severity Score (ISS) was 8.1. Forty-one per cent were cleared for discharge without follow-up. Twenty-seven per cent required ongoing neurocognitive therapy. Three per cent were deemed unsafe for discharge home. Of the patients cleared for discharge, 88 per cent had positive/questionable loss of consciousness (LOC), whereas 81 per cent who required additional therapy had positive/questionable LOC ( P = 0.20). Age, gender, ISS, and alcohol use were compared between the groups and not found to be statistically different rendering them poor predictors for appropriate discharge from the ED. A surprisingly high percentage (27%) of patients who would have met traditional ED discharge criteria were found to have persistent deficits after neurocognitive testing and were referred for ongoing therapy. We provide evidence to suggest that we should take pause before discharging patients with MTBI without a cognitive evaluation.